Problematika Pengembangan Ekstrakurikuler Di MI At- Taqwa Kebon Agung Sidoarjo - Rosmita sari; Fathul Fauzi (CV. Satria Jaya, 2025)
This research aims to analyze the problems and identify the supporting and inhibiting factors in extracurricular development at MI At-Taqwa Kebon Agung Sidoarjo.This research uses descriptive qualitative methods with a case study approach, this research involves the madrasah head, deputy madrasah head of student affairs, extracurricular coaches, and students as subjects. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman technique (data reduction, data display, conclusion drawing). The results of the study identified supporting and inhibiting factors. Supporting factors include: 1) Positive support from parents (permission, equipment, participation) and high commitment of teachers in guiding students. 2) Increased student motivation and achievement, demonstrated by enthusiastic participation and achievements in various fields such as sports, arts, and religion. 3) Strong school management policies in recruiting competent coaches and flexibility in forming new extracurricular activities. The inhibiting factors found were: 1) Uneven student participation, with some activities attracting many students but some with minimal interest or even not followed. 2) Limited facilities and infrastructure, such as inadequate field conditions or equipment and lack of specialized space. 3) The lack of funding, which limits the number, type of activities, and quality of extracurricular activities. This research is expected to provide strategic recommendations to improve the effectiveness of extracurricular development at MI At-Taqwa Kebon Agung Sidoarjo